Dextran sulfate sodium-induced colitis alters stress-associated behaviour and neuropeptide gene expression in the amygdala-hippocampus network of mice - Reichmann, Florian (Sci Rep, 2015)
Psychological stress causes disease exacerbation and relapses in inflammatory bowel disease (IBD) patients. Since studies on stress processing during visceral inflammation are lacking, we investigated the effects of experimental colitis as well as psychological stress on neurochemical and neuroendocrine changes as well as behaviour in mice. Dextran sulfate sodium (DSS)-induced colitis and water avoidance stress (WAS) were used as mouse models of colitis and mild psychological stress, respectively. We measured WAS-associated behaviour, gene expression and proinflammatory cytokine levels within the amygdala, hippocampus and hypothalamus as well as plasma levels of cytokines and corticosterone in male C57BL/6N mice. Animals with DSS-induced colitis presented with prolonged immobility during the WAS session, which was associated with brain region-dependent alterations of neuropeptide Y (NPY), NPY receptor Y1, corticotropin-releasing hormone (CRH), CRH receptor 1, brain-derived neurotrophic factor and glucocorticoid receptor gene expression. Furthermore, the combination of DSS and WAS increased interleukin-6 and growth regulated oncogene-α levels in the brain. Altered gut-brain signalling in the course of DSS-induced colitis is thought to cause the observed distinct gene expression changes in the limbic system and the aberrant molecular and behavioural stress responses. These findings provide new insights into the effects of stress during IBD.